2016
DOI: 10.1016/j.ijgo.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for robotic gynecologic procedures requiring conversion to other surgical procedures

Abstract: The overall incidence of conversion from robotic surgery to laparotomy was low. Higher body mass index, previous laparotomy, history of asthma, using a single-port approach, and surgeon case volume were associated with the risk of conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Five studies of hysterectomy and one study combining all robotic gynaecology procedures were included; these studies demonstrated mixed results [19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five studies of hysterectomy and one study combining all robotic gynaecology procedures were included; these studies demonstrated mixed results [19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Brunes et al did nd a signi cant relationship between surgeon volume and peri-operative outcomes, including blood loss and operative time [24]. Unger et al pooled all robotic gynaecological procedures in their analysis and demonstrated that higher surgeon volume was associated with reduced rates of conversion to an alternative procedure [20].…”
Section: Resultsmentioning
confidence: 99%
“…Common robotic gynecologic cancer surgery like pelvic and para-aortic lymphadenectomy can be associated with vascular injury. The incidence was about 1% [7,8], and was a major cause of conversion to laparotomy [12]. This can be caused by poor surgical view where the vessels are beyond the field of view, inadvertent clashing of robotic instrument which the surgeons are not aware of, or activating the wrong foot energy pedal.…”
Section: Inherent Risks Of Operationsmentioning
confidence: 99%
“…Unger et al28 attempted retrospectively to determine the incidence of, and risk factors for, conversion from robotic procedures to other surgical techniques. Patients’ demographic and perioperative data were retrieved, in addition to surgeon experience based upon monthly case volume.…”
Section: Robotic Surgery For Benign Indicationsmentioning
confidence: 99%